Microtype multimedia. (Cincinnati, OH : South-Western Educational, 1999)
This manual provides the necessary information to help you install the software and prepare it for use. Other sections didcuss each major feature of the Micro type Multimedia software. There are also troubleshooting tips that are provided in the event you run into any problems while using the program.
Keywords: Typewriting; Typewriting -- Problems, exercises, etc; Typewriting -- Problems, exercises, etc. -- Interactive multimedia